1999
DOI: 10.1080/j.1600-0412.1999.781004.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead and cadmium and birth weight among sub-arctic and arctic populations of Norway and Russia

Abstract: Maternal blood-lead level as an environmental factor is an apparent predictor of low birth weight and BMIC. It reduced substantially the contribution of a country factor in explaining the observed differences in birth weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 36 publications
(65 reference statements)
4
35
3
Order By: Relevance
“…Exposure to cadmium is a serious public health concern, and a number of previous studies have reported an inverse relationship between maternal cadmium exposure and infant body weight [11,13,[18][19][20][21][22]. In addition to occupational and environmental exposure, pregnant women are also exposed through smoking.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to cadmium is a serious public health concern, and a number of previous studies have reported an inverse relationship between maternal cadmium exposure and infant body weight [11,13,[18][19][20][21][22]. In addition to occupational and environmental exposure, pregnant women are also exposed through smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the literature regarding metal exposure and fetal growth outcomes is inconsistent. Some studies report an association (Rahman et al, 2009;Llanos and Ronco, 2009;Bellinger et al, 1991;Chen et al, 2006;Foldspang and Hansen, 1990;Hopenhayn et al, 2003;Kippler et al, 2011;Lee et al, 2010;Lin et al, 2011;Nishijo et al, 2004;Odland et al, 1999;Osman et al, 2000;Ramón et al, 2009;Shirai et al, 2010;Tian et al, 2009;Xie et al, 2013;Yang et al, 2003;Zhu et al, 2010) while others report no association (Odland et al, 1999;Osman et al, 2000;Ding et al, 2013;Daniels et al, 2007;Galicia-García et al, 1997;Jones et al, 2010;Sowers et al, 2002;Menai et al, 2012;Loiacono et al, 1992;Lucas et al, 2004). Few studies have examined low-level exposure as currently experienced in most developed countries such as Canada, thus any resultant health effects are relatively unknown.…”
mentioning
confidence: 87%
“…Other studies have found adverse associations of maternal B‐Cd with SGA and/or birthweight in models adjusted for smoking 14, 15, 16. Conversely, other studies have found no associations7, 9, 12, 30 or even beneficial associations31 with birthweight or SGA in models adjusted or stratified for smoking, even when mean or median maternal B‐Cd levels were high (>1 μg/L) 10, 32, 33. There is greater consensus for other birth outcomes (birth length or crown–heel length, head circumference, gestational age, preterm birth), with most studies finding no associations (see Table S5).…”
Section: Commentsmentioning
confidence: 98%
“…These diseases may be related to the role of Cd as an endocrine disruptor through interaction with hormone signalling pathways 4. Its effects on birth outcomes, however, particularly at moderate exposures, are not well understood and in this regard Cd has received far less research attention than its near neighbours in the periodic table, lead and mercury, The placenta is thought to be at least a partial barrier to Cd transfer to the fetus,5, 6 but determination of ratios of Cd in cord blood : maternal blood have left this in doubt (ratios ranging from 0.247 to 1.08,8 with others finding intermediate values9, 10). Studies with moderate maternal blood cadmium levels (B‐Cd; below a suggested reference value of 1 μg/L11) and adjustment for smoking have generally found no associations with birthweight, birth length, head circumference or preterm delivery,8, 12, 13 but other studies have found negative associations particularly with birthweight14, 15, 16 (Table S1).…”
mentioning
confidence: 99%